2020
DOI: 10.1111/scs.12947
|View full text |Cite
|
Sign up to set email alerts
|

Job rotation approach in nursing profession

Abstract: Background The nursing profession still needs more attention from decision‐makers to enhance satisfaction and commitment in the work environment. Aims and objectives This study aims to explore the perceived level of job rotation, job satisfaction, job commitment, job turnover and job conflict among nurses who previously had job rotation experience in Jordan. The study also investigates the correlation between studied variables and job rotation approach based on the type of hospitals. Furthermore, it also evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 32 publications
2
19
0
Order By: Relevance
“…One of the solutions to solve the problem of burnout among nurses is the job rotation approach. This approach helps nurses to have job satisfaction and commitment in their workplace [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of the solutions to solve the problem of burnout among nurses is the job rotation approach. This approach helps nurses to have job satisfaction and commitment in their workplace [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Job Rotation Scale was used to measure the perceived level of job rotation among both participating nurses in this study. This scale consisted of 9 items and has been used according to previous studies of 2,18 Correlation coefficients ranged between 0.61 and 0.91. Regarding the reliability of the job rotation scale, internal consistency achieved the required level of Cronbach's alpha and was 0.85.…”
Section: Job Rotation Scalementioning
confidence: 99%
“…Moreover, job satisfaction is positively correlated with employee performance 14 . A study conducted in Sri Lanka showed that job rotation had a positive effect on job satisfaction 7 , and more recently in Jordan, they found that applying job rotation approach among nurses, raised commitment, which indicates that commitment plays a significant role in the job rotation approach 2 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations